Perkembangan Children's Literature dalam Folklor di Perpustakaan: Studi Content Analysis - Evi Nursanti Rukmana; Kusnandar Kusnandar (Jurnal Pustaka Ilmiah, 2021)
Folklore is a form of children's literature. Libraries can provide a collection of folklore for children among users in introducing local culture and language. So folklore has been researched by several researchers from various countries. This study aims to determine the development of children's literature in folklore in the library. The research method used a qualitative approach through the content analysis method. The references studied were from seven references which were then mapped into several categories. Based on analysis 7 reference, all the folktales characters can psychology and phisic analysis. Folklore can retall to stundents at the school through storytelling and folklore reproduction on modul at school. Folklore is representation of culture at the region. The collection of folklore is the one of unique collection at the library. Based on seven reference, the most widely written folklore research is the theme of storytelling which is researched from 3 references. The research method that is widely used is the literature study method used from 3 references. Types of folklore that have been studied are folk stories written 6 times, poetry written 5 times, epic stories (struggles) and songs written 3 times, animal tales, legends, historical stories, myths, proverbs and written utterances respectively. 2 times, and other types of folklore are written once. The conclusion of this study shows that folklore can be researched from a variety of sciences, folklore as an effective learning medium in schools and libraries, folklore reproduction enriches children's literature in the realm of education.